MiR‐203 induces oxaliplatin resistance in colorectal cancer cells by negatively regulating ATM kinase. Issue 1 (8th October 2013) - Zhou, Yunfei; Wan, Guohui; Spizzo, Riccardo; Ivan, Cristina; Mathur, Rohit; Hu, Xiaoxiao; Ye, Xiangcang; Lu, Jia; Fan, Fan; Xia, Ling; Calin, George A.; Ellis, Lee M.; et al.
Abstract : Chemotherapy for patients with metastatic colorectal cancer (CRC) is the standard of care, but ultimately nearly all patients develop drug resistance. Understanding the mechanisms that lead to resistance to individual chemotherapeutic agents may help identify novel targets and drugs that will, in turn, improve therapy. Oxaliplatin is a common component combination therapeutic regimen for use in patients with metastatic CRC, but is also used as a component of adjuvant therapy for patients at risk for recurrent disease. In this study, unbiased microRNA array screening revealed that the miR‐203 microRNA is up‐regulated in three of three oxaliplatin‐resistant CRC cell lines, and therefore we investigated the role of miR‐203 in chemoresistance. Exogenous expression of miR‐203 in chemo‐naïve CRC cells induced oxaliplatin resistance. Knockdown of miR‐203 sensitized chemoresistant CRC cells to oxaliplatin. In silico analysis identified ataxia telangiectasia mutated (ATM), a primary mediator of the DNA damage response, as a potential target of miR‐203. ATM mRNA and protein levels were significantly down‐regulated in CRC cells with acquired resistance to oxaliplatin. Using TCGA database, we identified a significant reverse correlation of miR‐203 and ATM expression in CRC tissues. We validated ATM as a bona fide target of miR‐203 in CRC cells. Mutation of the putative miR‐203 binding site in the 3′ untranslated region (3′UTR) of the ATM mRNA abolished the inhibitory effect of miR‐203 on ATM. Furthermore, stable knockdown of ATM induced resistance to oxaliplatin in chemo‐naïve CRC cells. This is the first report of oxaliplatin resistance in CRC cells induced by miR‐203‐mediated suppression of ATM. Highlights: miR‐203 was up‐regulated in oxaliplatin‐resistant colorectal cancer (CRC) cells. Knockdown of miR‐203 sensitized chemoresistant CRC cells to oxaliplatin. ATM levels were significantly down‐regulated in oxaliplatin‐resistant CRC cells. Stable knockdown of ATM induced resistance to oxaliplatin in chemo‐naïve CRC cells. Oxaliplatin resistance in CRC cells induced by miR‐203‐mediated suppression of ATM.